Analisis Lokasi Sekolah SMA yang Ideal di Kabupaten Bone Bolango dengan Sistem Informasi Geografis - Antu, Arjun B (Universitas Negeri Gorontalo, 2022)
In Indonesia, the problem of educational equity is still a serious problem, there are still few schools and the distance between most students' homes and schools is quite far from the school location. This study aims to determine the location of the ideal high school in Bone Bolango Regency by using a Geographic Information System. The location of this research was carried out in Bone Bolango Regency, the schools studied were SMA Negeri 1 Tapa, SMA Negeri 1 Kabila, SMA Negeri 1 Suwawa, SMA Negeri 1 Suwawa Timur, SMA Negeri 1 Bone, SMA Negeri 1 Bone Pantai, SMA Negeri 1 Bulango Ulu. , SMA Negeri 1 Pinogu, SMAS Terpadu Wirabakti. The method used in the research is a survey, interviews and then given a score with predetermined criteria. Primary data is obtained directly through observations, field measurements and interpretation of satellite imagery. In this study, the primary data were land area for education units, slope, accessibility, free of disasters and landslides, educational reach, and number of students. Secondary data is obtained from information, statistical data and data derived from existing field data. In this study the secondary data is the distribution of high school schools. The time of the study was conducted for 6 months from February to July. The research results are based on parameters with certain criteria, namely land area for education units, slope, accessibility, free of disasters and landslides, and educational reach. Then the five parameters are scored and the results are overlaid into an ideal school map.